2015
DOI: 10.1093/jxb/erv043
|View full text |Cite
|
Sign up to set email alerts
|

Aequorin-based luminescence imaging reveals differential calcium signalling responses to salt and reactive oxygen species in rice roots

Abstract: HighlightBased on the aequorin system, we describe the establishment of a calcium reporter line in rice and test the responses of the reporter towards salt and oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 50 publications
2
24
0
Order By: Relevance
“…To date, only 2 aequorin transgenic rice articles have been reported. 27,32 To investigate the Ca 2C and protein phosphorylation changes induced by microbe/ pathogen-associated molecular patterns (MAMPs/PAMPs), Kurusu et al (2011) established a transgenic rice cell line stably expressing apoaequorin and characterized the interrelationship between MAMP-induced changes in Ca 2C , production of reactive oxygen species (ROS) and protein phosphorylation. 27 Despite the progress achieved by rice culture cells, stable transgenic rice expressing apoaequorin is needed to investigate the changes of Ca 2C in response to various environmental stimuli in rice.…”
Section: Identification Of Important Genes By Screening Ca 2c Insensimentioning
confidence: 99%
See 2 more Smart Citations
“…To date, only 2 aequorin transgenic rice articles have been reported. 27,32 To investigate the Ca 2C and protein phosphorylation changes induced by microbe/ pathogen-associated molecular patterns (MAMPs/PAMPs), Kurusu et al (2011) established a transgenic rice cell line stably expressing apoaequorin and characterized the interrelationship between MAMP-induced changes in Ca 2C , production of reactive oxygen species (ROS) and protein phosphorylation. 27 Despite the progress achieved by rice culture cells, stable transgenic rice expressing apoaequorin is needed to investigate the changes of Ca 2C in response to various environmental stimuli in rice.…”
Section: Identification Of Important Genes By Screening Ca 2c Insensimentioning
confidence: 99%
“…A recently published article introduced recombinant aequorin into rice and examined the change in Ca 2C in response to salt and ROS stresses. 32 In that paper, the apoaequorin gene was constitutively expressed under control of 35S promoter. The results revealed that the aequorin-based luminescence signal was only observed in roots, but RT-PCR showed that apoaequorin was expressed in all tissues.…”
Section: Identification Of Important Genes By Screening Ca 2c Insensimentioning
confidence: 99%
See 1 more Smart Citation
“…Pioneering studies have demonstrated that Arabidopsis seedlings expressing the bioluminescent Ca 2+ reporter protein aequorin exhibit a rapid rise in intracellular Ca 2+ ( [Ca 2+ ]i ) within seconds upon stimulation by NaCl solution (5,6). This rapid osmoticinduced Ca 2+ response has been observed in plant species ranging from rice (7) to the basalbranching moss taxon Physcomitrella patens (8), indicating that this response may be conserved across the Plantae kingdom. Solutions of either NaCl or iso-osmotic mannitol/sorbitol induce nearly identical rapid Ca 2+ responses, indicating that the nature of this rapid stimulus is largely osmotic rather than ionic (5,9,10).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the lack of similar system, no calcium sensors have been reported in rice. Recently, Zhang et al introduced recombinant aequorin into rice (Oryza sativa) and examined the change of Ca 2+ concentration in response to salt and H 2 O 2 stresses [7]. Because typical forward genetic screening is always useful to find genes involved in Ca 2+ signaling, this newly established system can be used to identify novel Ca 2+ -coupled stress sensors or pathways in rice after the establishment of an EMSmutagenized population.…”
mentioning
confidence: 99%